REPRESENTASI BOYS LOVE DALAM SERIAL ANIME YURI!!! ON ICE - Mufrida Ardiana; Nita Rimayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Yuri on ice is a television anime series about ice skating that is widely discussed by critics about packaging boys love in anime in a different way than most boys love genre anime. Boys love can be briefly explained as a term used to refer to love between man and man. Love between man and men in Indonesia is often reffered to as homo, which slowly begins to blend in our society. Therefore, this research aims to find out how boys love is represented in the anime series Yuri!!! On Ice seen from the level of reality, the level of representation and the level  of ideology.This research uses qualitative research methods and supported by John Fiske’s seiotic analysis theory. The subjects and objects in this research were observations of audio and visual displays in scenes from the anime series Yuri!!! On Ice with data collection techniques used are, observation, documentation, and literature study.The results of this research indicate that there is a representation of boys love in the anime series Yuri!!! On Ice. Boys love representation in the anime series Yuri!!! On Ice obtained using John Fiske’s semiotic analysis through the level of reality, the level of representation, and the level of ideology are: metrosexual men, beautiful men, people who don’t care about other people’s views, people who have romantic personalities, and eternal partners. Keyword: Boys Love, Anime, Representation, Semiotic